Strong electro-optically active Ni-substituted Pb(Zr0.35Ti0.65)O3 thin films : toward integrated active and durable photonic devices - Zhu, Minmin (2020)
Ferroelectric materials for precise control of light from lasers to optical communications have sparked great interest owing to their large electro-optic (EO) coefficients, low propagation loss, and fast switching time. Here, we report the deposition of highly oriented Ni-doped lead zirconate titanate (PZT) thin films on glass substrates as a novel way to seamlessly connect the electrical, optical, and magnetic domain. Small dielectric dispersion, low dielectric loss, and a large dielectric constant ranging from 102 Hz to 106 Hz were observed at a Ni content of 0.5 mol%. These films show well-saturated ferroelectric hysteresis with a large spontaneous polarization (>30 μC cm−2) and a high Curie temperature (>350 °C). In addition, optical measurements indicate a large refractive index (∼2.43), a low propagation loss (∼4.14 dB cm−1), a fast response time (4.02 μs), and an effective EO coefficient (167.7 pm V−1), which are five times larger than those of the current standard material for EO devices (LiNbO3). More importantly, such films can work well up to 250 °C and retain above 80% of the EO performance at 104 Hz. Finally, the substitution of Ni2+ at the Ti4+ site shows distinct magnetic behaviors. The integration of EO active films could pave the way for future power-efficient, ultrafast switches, and compact integrated nanophotonic and magneto-optic devices.